Kajian laju timbulan sampah di Yogyakarta selama pandemi Covid-19 - Suhardono, Sapta; Septiariva, Iva Yenis; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
The Covid-19 pandemic has resulted in restrictions on people's daily activities. Including the Yogyakarta area which is famous for its tourism and education center. Changes indirectly allow changes in the rate of waste generation. The purpose of this study was to determine changes in the generation of waste generated in Yogyakarta during the pandemic and before. This study uses secondary data for data on waste generation and population in Yogyakarta City, Sleman Regency, and Gunung Kidul Regency. Analysis was performed using analysis of variance (ANOVA) with software. Waste generation in district areas tends to decrease compared to urban areas. However, judging from the rate of waste generation, the Yogyakarta City tends to decrease, while in the district it is increasing. When viewed from the ANOVA test, there was no significant change in waste generation during the Covid-19 pandemic. This also needs to be a concern where a decrease in waste generation is not always followed by a decrease in the rate of waste generation.